A review of the uto-aztecan premolar trait in south america and its presence in Colombia - Rodríguez-Flórez, Carlos David (Revista Facultad de Odontología Universidad de Antioquia, 2014)
Introduction: the so-called Uto-Aztecan premolar (hereinafter UAP) or distal-sagittal crest of upper premolars is a rare morphologic trait that appears in the first premolars of American Indian groups only. It is described as the presence of a pronounced crest extending from the tip of the buccal cusp (paracone) towards the distal-occlusal edge, almost reaching the sagittal sulcus. The objective of this study was to describe the presence of UAP in South America and its relation with Colombian indigenous populations. Methods: a total of 495 individuals recorded in the literature were collected. Conventional descriptive statistics was used to observe asymmetry and atypical variables. Comparisons were made using Smith’s mean measure of divergence. Results: the spreading of this trait in South America might have been due to interactions between the groups represented by two biological components observed in the calculated matrix. Discussion: the Pacific Ocean coast and the valleys that connect the Andean and Amazonian regions coupled with their main rivers should have played a role in the rapid spread of this trait in samples located as far apart as Minas Gerais (Brazil) and Punta Teatinos (Chile). Conclusions: UAP is present in Colombia since about 3000 BP (before present). This trait should be evaluated in mestizo groups.